INTRODUKSI PENCEGAHAN KEBAKARAN LAHAN PERTANIAN DI AREA GAMBUT PADA ANAK USIA SEKOLAH DASAR - Suharyani, Anita; ,, Maswadi; Oktoriana, Shenny (Universitas Tanjungpura, 2019)
Burning behavior in the peatland area in Bengkayang District is still running which is caused many disadvantages. To solve it, we need to prevention and handling activities. prevention activity is better to do which is the target all the society include children. children have imitation characteristic, include burning behavior. therefore, the introduction of land burning prevention necessary to do with fun method and media.Â This activity was conducted in SDN 4 Sungai Jaga A Sungai Raya Sub-district Bengkayang district as much as 31 students in fourth grade. The methodology that was used with lecturer and tale and used the poster, puppets, and banner as media. Participants very excited when activities occur. hopefully, children have the knowledge, commit good behavior and concern to their environment.Â